MR T1-Weighted Inversion Recovery Imaging in Detecting Brain Metastases: Could It Replace T1-Weighted Spin-Echo Imaging? - Qian, Y.-F.; Yu, C.-L.; Zhang, C.; Yu, Y.-Q. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: T1-weighted inversion recovery (T1IR) imaging demonstrates higher brain tissue contrast and is more sensitive to contrast enhancement than T1-weighted spin-echo (T1SE) imaging. However, the effectiveness of the 2 imaging sequences in detecting brain metastases has not been studied. The objective of this report was to determine which sequence should be used for detecting brain metastases by comparing the effectiveness of T1IR imaging with that of T1SE imaging.Materials and METHODS: Thirty-one patients with brain metastases underwent T1SE and T1IR with and without intravenous gadopentetate dimeglumine. T1SE and T1IR images were compared for the number of metastases, degree of contrast enhancement, volume and contrast-to-enhancement ratio (CER) of tumors, and contrast ratio (CR) of tumor to white matter (WM), tumor to gray matter (GM), and tumor to CSF.RESULTS: There were 352 metastases in 31 patients, among which 2 patients with 5 metastases were demonstrated only on postenhanced T1SE images. Pre-enhanced and postenhanced T1SE images detected 162 and 350 lesions, respectively, whereas pre-enhanced and postenhanced T1IR images only discovered 94 and 233 lesions. The degree of tumor contrast enhancement was higher on T1IR images than on T1SE images, whereas no difference in the CER of tumors was found between the 2 sequences. Before enhancement, all of the CRs on T1IR images were higher than on T1SE images. After contrast enhancement, CRs of tumor to WM and tumor to GM were higher on T1SE images than on T1IR images. On the contrary, the CR of tumor to CSF was higher on T1IR images than on T1SE images. Tumor volumes were 5.6 ± 7.0 cm3 on postenhanced T1SE images and 5.5 ± 7.0 cm3 on postenhanced T1IR images, and no significant difference was found between the 2 groups.CONCLUSION: T1SE, but not T1IR, should be used as T1-weighted imaging in detecting brain metastases, because T1SE imaging has a greater sensitivity than T1IR imaging both before and after contrast material administration.